Urban Political Ecology in Mexico: Metabolism, conflicts, and the need for transformational pathways in the Valley of Mexico, Guadalajara, and Monterrey - Ana Karen Jiménez Caballero; Diego Sebastián Vidal Origel; Gian Carlo Delgado Ramos; Laura Elena Castro Sánchez (Journal of Political Ecology, 2023)
This article analyzes urban socio-ecological conflicts in the Mexican metropolitan areas of the Valley of Mexico, Guadalajara and Monterrey from an Urban Political Ecology (UPE) approach. We identify the main triggers of such urban socio-ecological conflicts and the causal links between actors, resources and spaces which make up the uneven production of urban space. This focus includes unequal access to resources, uneven distribution of environmental impacts, and the rise of contestation. We outline UPE theoretically and conceptually, and delineate what is meant by urban socio-ecological conflict. UPE is then contextualized within Mexico's contemporary urbanization process as a prelude for characterizing case studies (including their metabolic profiles) and the analysis of prevailing socio-ecological conflicts. For the latter, we identify the main urban conflicts in the years 2012 and 2022, highlighting some of the main characteristics, similarities, and discontinuities across three metropolitan areas. In the face of an increasing metabolism of contemporary urbanization, we conclude with a brief consideration of the potential role of socio-ecological conflicts for enabling alternative forms of urban space production, particularly through the agency of social movements, including their capacity to propose and build "urban spaces of hope."